Children's Rights: Social Representations of Boys and Girls in Rural Areas in Uruguay - Cauci Becerra, Adriana Inés (2024)
The study explores the social representations of children's rights to understand the perceptions and meanings attributed to these rights in the daily lives of the boys and girls at Rural School No. 98 in Colonia Damón. Adopting a qualitative approach based on the theory of social representations, the research involved direct participant observation and discussion workshops with the participating children. The study reveals the voices and perspectives of the children, emphasizing the importance of being heard and respected, as well as the actions taken to ensure that these rights are fulfilled. Recognized rights that emerge include the rights to identity, play, and living in the countryside, which are integrated into the productive and reproductive activities of the families. It is important to consider incorporating pedagogical methodologies with an artistic focus in early childhood and primary education centered on children's rights. This approach could serve as a catalyst to address the daily challenges faced by children while fostering the recognition of their rights to ensure their full exercise. Playful approaches and educational strategies centered on children's rights are identified as appropriate to enhance these rights.